Quark Confinement and the Hadron Spectrum V 2003
DOI: 10.1142/9789812704269_0030
|View full text |Cite
|
Sign up to set email alerts
|

Color Confinement and Dual Superconductivity in Full QCD

Abstract: We report on evidence that confinement is related to dual superconductivity of the vacuum in full QCD, as in quenched QCD. The vacuum is a dual superconductor in the confining phase, whilst the U (1) magnetic symmetry is realizedà la Wigner in the deconfined phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…[8][9][10] it has been shown that µ is different from zero in the confined phase of SU (2) and SU(3) pure gauge theories, that it goes to zero at the deconfining phase transition, and that this is independent of the abelian projection chosen to define the magnetic charge. The same has also been verified in the case of full QCD [11].…”
Section: Introductionsupporting
confidence: 68%
“…[8][9][10] it has been shown that µ is different from zero in the confined phase of SU (2) and SU(3) pure gauge theories, that it goes to zero at the deconfining phase transition, and that this is independent of the abelian projection chosen to define the magnetic charge. The same has also been verified in the case of full QCD [11].…”
Section: Introductionsupporting
confidence: 68%
“…µ is indeed a disorder parameter for the deconfining phase transition. This analysis has been extended to full QCD with similar results [10,11] and an extension to SU(N ) is on the way [12]. In the full QCD case the Polyakov line is not an order parameter and the transition is indicated by a drop of the chiral condensate, which is not either an order parameter at non-zero quark mass, so that µ is the only available (dis)order parameter and could provide a genuine criterion for confinement.…”
Section: Introductionmentioning
confidence: 97%
“…Our conclusion is that dual superconductivity is the mechanism of confinement. The disorder parameter µ detects it, both in pure gauge and in full QCD 20 , as expected in the philosophy of N C → ∞: indeed quark loops are non leading in that expansion, and the mechanism of confinement is expected to be the same with and without quarks. A carefull analysis of the relation between µ and the chiral order parameter is on the way.…”
Section: Discussionmentioning
confidence: 56%